Eight-year dry deposition of atmospheric mercury to a tropical high mountain background site downwind of the East Asian continent. (December 2019) - Phu Nguyen, Ly Sy; Zhang, Leiming; Lin, Da-Wei; Lin, Neng-Huei; Sheu, Guey-Rong
Abstract: Atmospheric deposition, either dry or wet, has been identified as an important pathway of mercury (Hg) input to terrestrial and aquatic systems. Although East Asia is the major atmospheric Hg emission source region, very few studies have been conducted to quantify atmospheric Hg deposition in its downwind region. In this study, 8-year (2009–2016) atmospheric Hg dry deposition was reported at the Lulin Atmospheric Background Station (LABS), a high mountain forest site in central Taiwan. Dry deposition of speciated Hg was estimated using a bi-directional air-surface flux exchange model for gaseous elemental mercury (GEM) and dry deposition models for gaseous oxidized mercury (GOM) and particulate-bound mercury (PBM), making use of the monitored speciated atmospheric Hg concentrations. Annual total Hg dry deposition ranged from 51.9 to 84.9 μg m −2 yr −1, with a multi-year average of 66.1 μg m −2 yr −1 . Among the three forms of atmospheric Hg, GEM was the main contributor to the total dry deposition, contributing about 77.8% to the total, due to the high density of forest canopy as well as the much higher concentration of GEM than GOM and PBM at LABS. Mercury dry deposition is higher in winter and spring than in summer and fall, partly due to the elevated Hg concentrations associated with air masses from East and Southeast Asia where with high atmospheric Hg emissions. The mean annual dry/wet deposition ratio of 2.8 at LABS indicated that Hg deposition to forest landscape was governed by dry rather than wet deposition. Graphical abstract: Image 1 Highlights: First multi-year dry deposition estimation of speciated atmospheric Hg to a tropical mountain site downwind of East Asia. GEM was the major dry deposition contributor due to its higher concentrations and the high density of forest canopy. Hg deposition to this forest landscape was governed by dry rather than wet deposition. Both dry and wet Hg depositions at this tropical mountain site were higher than those reported from the temperate region. Abstract : Elevated atmospheric Hg deposition found at this mountain forest site has important implications in Southeast Asia where land covers of mountains are mostly forests.